Does tax aggressiveness and cost of debt affect firm performance? The moderating role of political connections - Abdullah; Muhammad Arsalan Hashmi; Abdul Mateen; Yousuf Ali Badshah; Muhammad Sikander Iqbal (Cogent Economics & Finance, 2022)
Firms in emerging economies continue to suffer as a consequence of tax evasion, high cost of financing, political interference, weak governance systems, and bureaucratic institutions. In order to understand how these challenges complicate commercial activities, this study examines how tax aggressiveness, cost of debt, and political connections affect firm performance in Pakistan. Unlike previous research, we also explore if political connections moderate the association between (i) tax aggressiveness and firm performance and (ii) cost of debt and firm performance. Our robust empirical analysis reveals that tax aggressive firms have weaker performance while politically connected firms have better performance, ceteris paribus. Further, we find that tax aggressive firms having politically connected board members have better performance as compared to their non-connected counterparts. Similarly, firms with a high cost of debt and politically connected board members have better performance as compared to non-connected firms. Thus, we argue that political connections help connected firms in overcoming the adverse consequences of tax aggressiveness and the high cost of debt through their influence in procuring government projects, subsidies, and other benefits. Therefore, policymakers are advised to restrict politically connected board members from extending favors and concessions to connected firms. We also encourage shareholders to exercise their voting power and monitoring capabilities for mitigating agency problems inherent in politically connected firms.
Keywords: 330; cost of debt; firm performance; political connections; tax aggressiveness